2010
DOI: 10.1182/blood-2009-07-230268
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel downstream targets of platelet glycoprotein VI activation by differential proteome analysis: implications for thrombus formation

Abstract: Platelets play a key role in hemostasis and various diseases including arterial thrombosis. Glycoprotein VI (GPVI) mediates adhesion to collagen structures exposed at sites of vascular injury and subsequent platelet activation. We determined the effects of specific activation of GPVI on the human platelet proteome. Isolated human platelets were stimulated with an activating monoclonal antibody specific for GPVI. Platelet proteins were analyzed by 2-dimensional difference gel electrophoresis (2D-DIGE) and mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 52 publications
2
37
0
Order By: Relevance
“…In response to 1 μg/ml collagen, the aggregation in 25 mmol/l glucose was 25% higher than that in 5.5 mmol/l glucose and was attenuated by treatment with 1-10 μmol/l epalrestat ( Figure 3, A-C), suggesting that such aggregation was abolished by inhibition of AR. The concentration of epalrestat used in the present study was based on the dose-response curve (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI59291DS1), which is consistent with previous studies (14). To corroborate the spectrophotometric aggregation assays, P selectin, the marker for platelet activation, was analyzed using flow cytometry.…”
Section: Tx Biosynthesis In Vivo In Dm Patients Versus Non-dm Patientsupporting
confidence: 52%
See 1 more Smart Citation
“…In response to 1 μg/ml collagen, the aggregation in 25 mmol/l glucose was 25% higher than that in 5.5 mmol/l glucose and was attenuated by treatment with 1-10 μmol/l epalrestat ( Figure 3, A-C), suggesting that such aggregation was abolished by inhibition of AR. The concentration of epalrestat used in the present study was based on the dose-response curve (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI59291DS1), which is consistent with previous studies (14). To corroborate the spectrophotometric aggregation assays, P selectin, the marker for platelet activation, was analyzed using flow cytometry.…”
Section: Tx Biosynthesis In Vivo In Dm Patients Versus Non-dm Patientsupporting
confidence: 52%
“…Important questions remained as to the mechanism and how this relates to our initial clinical observations of increased TX-M in DM patients despite the use of ASA (Figure 1). Interestingly, a recent study using 2D difference gel electrophoresis and mass spectrometry demonstrated that AR expression and its activity contribute to the human platelet activation after stimulation of the glycoprotein VI (GPVI) receptor by collagen (14). AR is known to metabolize glucose to sorbitol.…”
Section: Tx Biosynthesis In Vivo In Dm Patients Versus Non-dm Patientmentioning
confidence: 99%
“…In one study, proteins from resting and collagen receptor-stimulated platelets were incubated with cAMP/cGMP-coupled beads, and the pull-down eluates were analyzed by LC-MS/MS. 115 Owing to the enrichment provided by specific probes, activity-based protein profiling 116-121 B, These studies are mainly (40%) based on 2-dimensional gel electrophoresis (2-DE)/ difference gel electrophoresis (DIGE), 46,52,53,80,82,83,85,87,88,90,91,[93][94][95][96]98,102,106,110,112,113 whereas gelfree methods (23%) are still under-represented. 21,42,89,97,[114][115][116][117][118]121 Combination refers to studies using 2-DE/DIGE in combination with other approaches.…”
Section: Platelet Subproteomesmentioning
confidence: 99%
“…In contrast, state-of-the-art procedures use quantitative phosphoproteomics to monitor changes in phosphorylation levels of hundreds to thousands of peptides from relatively low sample amounts (≈0.1-1 mg of protein per condition), thus providing valuable insights into important biochemical processes. To date, mostly gel-based approaches in conjunction with phosphotyrosine immunoprecipitation have been used to study platelet signaling processes (eg, mediated by activation of thrombin receptors, 93,106,107,137 collagen receptors, 82,112 C-type lectin-like receptor 2, 138 and integrin α IIb β 3 outside-in signaling). 139 Because of the limitation in sensitivity, these approaches often did not provide MS-based identification of phosphorylation sites but identified new phosphoproteins and signaling pathways, hence expanding the knowledge about platelet regulation.…”
Section: Ptm and Signaling Proteomics In Plateletsmentioning
confidence: 99%
“…It maintains bleeding time within limit during various traumatic conditions and erosions of capillaries. 3 The platelets carry different role in circulating blood as follows: 1. Adhesion to collagen fibrils of damaged vessel walls and releases serotonin, adenosine triphosphate (ATP) and adenosine diphosphate (ADP).…”
Section: Introductionmentioning
confidence: 99%